Exhausting the Sayings (Ahadeeth) in "Fateh Albari" "Saheeh Albkhari" Explanation from Al Boyoo' Book Up to the End of "Al – Makateb" Book - Samer Najeh Abdullah Samarah (My University, 2005)
I concluded the following from my search: 1.The number of sayings I exhausted from Al- Boyoo' book end of Al- Makateb was 272 of which 60 were exhausted in Saheh Muslim 2.I found out that Ibn Hijr gave his judgment on some of the sayings and left the others without judgment. 3. I agreed with Ibn Hijr on some and disagreed with his on others. 4. It appeared to me that Ibn hijr's approach was not firm enough on judging the sayings. 5. There were seven of the sayings concerned of which are not trust worthy. Thank Allah whose blessing is fulfilling the good deeds

خلصت من بحثي هذا إلى النتائج التالية: 1.عدد الأحاديث التي قمت بتخريجها من كتاب البيوع وحتى نهاية كتاب المكاتب 272 حديثاً منها 60 حديثاً أخرجها مسلم في صحيحه. 2.وجدت لابن حجر أحكاماً على بعض الأحاديث وترك الباقي بدون حكم 3.وافقت ابن حجر في أحكامه على بعض الأحاديث وخالفته في بعضها الاخر. 4.تبين أن منهج ابن حجر في الحكم على الأحاديث كان فيه شيء من التساهل 5. ﻭﻗﻊ ﻓﻲ ﺍﻷﺤﺎﺩﻴﺙ ﻤﻭﻀﻭﻉ ﺍﻟﺒﺤﺙ ﺴﺒﻌﺔ ﺃﺤﺎﺩﻴﺙ ﺃﺴﺎﻨﻴﺩﻫﺎ ﻭﺍﻫﻴﺔ. ﻭﺍﻟﺤﻤﺩ ﷲ ﺍﻟﺫﻱ ﺒﻨﻌﻤﺘﻪ ﺘﺘﻡ ﺍﻟﺼﺎﻟﺤﺎﺕ
تخريج الأحاديث الواردة في كتاب "فتح الباري شرح صحيح البخاري" من كتاب البيوع إلى نهاية كتاب المكاتب